The relationship between union membership and net fiscal impact - Sojourner, Aaron; Pacas, José (Bonn, 2018)
"This paper develops the first evidence on how individuals' union membership status affects their net fiscal impact, the difference between taxes they pay and cost of public benefits they receive, enriching our understanding of how labor relations interacts with public economics. Current Population Survey data between 1994 and 2015 in pooled cross-sections and individual first-difference models yield evidence that union membership has a positive net fiscal impact through the worker-level channels studied."